(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose – This study aimed to examine elementary school students’ critical thinking skills and their impact. Methodology – This research was a qualitative case study. The subjects of this study were 29 fifth-grade students and three teachers at an elementary school, chosen by a purposive sampling technique. Data were collected through observation, interviews, and critical thinking skills tests with open description types. The data validation technique used triangulation, applied to the study’s methods, sources, and theories. The data analytical framework of this research employed Milles and Hubberman’s (1994) interactive analysis model with the following stages: data validity, data collection, data reduction, data presentation, and drawing conclusions. Findings – Based on the research result analysis and discussion, only 10% of students whose scores were above the minimum completeness criteria from the school, and the class average only reached 50 out of 100. The scores on each indicator of critical thinking skills from the highest to the lowest, respectively, were inference with an average of 70, analysis with an average of 63, interpretation with an average of 56, and explanations with an average of 50. This low critical thinking skill was caused by students’ mistakes in answering the test questions. This research concluded that elementary school students’ critical thinking skills were still very low and caused by student factors: (a) students’ answers were not systematic; (b) students identified questions incorrectly and simply summarized the questions, then using them as answers directly; (c) misconception; (d) students relied on memory, not understanding. Meanwhile, the teacher factors comprised: (a) the learning model used by the teachers was dominant in the direct learning model with the lecture method; (b) the problem description provided was not familiar for students; (c) the problem and its resolution strategy offered did not make the students understand; (d) the teachers did not understand the material, lacked expertise in delivering the material, and used the textbook as the only source of information and delivery content. Significance – The study results indicated that the elementary school students’ critical thinking skills were still low due to several factors. These factors were originating mainly from the students and teachers themselves. The implication is that the school needs to pay more attention to strategies to improve and develop students’ critical thinking skills in the future. The findings can be used as a reference point when considering the planning of effective strategies to improve the teaching and learning of critical thinking skills in elementary schools.